Pengaruh Non Performing Loan (NPL) dan Loan to Deposit Ratio (LDR) terhadap Return On Asset (ROA) dengan Capital Adequacy Ratio (CAR) sebagai Variabel Intervening Pada PT Bank Artha Graha Internasional, Tbk. - Ferdinand S Manalu; Partogi Saoloan Samosir; Abdul Rivai (Jurnal Ekonomi dan Industri, 2024)
This study aims to analyze the effect of Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on Return On Assets (ROA), to analyze the effect of Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on Capital Adequacy Ratio (CAR). ), analyzing Return On Asset (ROA) to Capital Adequacy Ratio (CAR), analyzing Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) to Return On Assets (ROA) through Capital Adequacy Ratio (CAR) at PT Bank Artha Graha Internasional Tbk. In this study, the research design used causality between variables and the research method used also described the relationship or influence between variables. The data collection technique uses 2 types of data collection, namely secondary data and primary data. The analysis technique used in this research is Path Analysis. Path analysis is an analysis to determine the magnitude of the contribution of the influence of each variable x to y using regression with standardized variables. The results showed that the results of the effect of Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on Return on Assets (ROA) through Capital Adequacy Ratio (CAR) can act as an intervening variable. The calculation results obtained indicate that the total effect of each exogenous variable is greater than the direct effect on Return on Assets (ROA). These results indicate that the Capital Adequacy Ratio (CAR) can play a role as an intervening variable between Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) to Return On Assets (ROA) in the case of PT Bank Artha Graha Internasional Tbk.